2019
DOI: 10.1038/s12276-019-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic analysis in rheumatoid arthritis synoviocytes

Abstract: Rheumatoid arthritis (RA) is a complex chronic systematic disease with progressive destruction of the joints by invasive synoviocytes. To characterize the key regulators involved in the development of RA, we obtained multilayer epigenomics data including DNA methylation by whole-genome bisulfite sequencing, miRNA profiles, genetic variations by whole-exome sequencing, and mRNA profiles from synoviocytes of RA and osteoarthritis (OA) patients. The overall DNA methylation patterns were not much different between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 85 publications
1
25
0
2
Order By: Relevance
“…In OA chondrocytes, transfection of transcription factor AP-2ε led to increased expression of CXCL1 , one of the chemokines inducing chondrocyte hypertrophy and apoptosis in OA 75. Two recent studies also suggested TFAP2A is potentially one of the novel transcription regulators in psoriatic skin 76 and RA synoviocytes 77 through sequencing and bioinformatics approach. Taken together, we proposed the up-regulated TFAP2A in OA synovial tissue may represent higher degree of inflammation in OA, and TFAP2A may be a novel target for anti-inflammatory therapy in arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…In OA chondrocytes, transfection of transcription factor AP-2ε led to increased expression of CXCL1 , one of the chemokines inducing chondrocyte hypertrophy and apoptosis in OA 75. Two recent studies also suggested TFAP2A is potentially one of the novel transcription regulators in psoriatic skin 76 and RA synoviocytes 77 through sequencing and bioinformatics approach. Taken together, we proposed the up-regulated TFAP2A in OA synovial tissue may represent higher degree of inflammation in OA, and TFAP2A may be a novel target for anti-inflammatory therapy in arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…For example, compared with osteoarthritis (OA), 523 low-methylated regions are specific to RA. The regions overlap with specific motifs of transcription factors, such as GLI1, RUNX2 , and TFAP2A/C , which promote the proliferation of synovial cells and the development and migration of plasmacytoid dendritic cells in RA ( Ham et al, 2019 ). In contrast with OA, in which C18orf45, LMO4, MAP3K5, ODZ4, PKNOX2, SEPT11, MSRA , and MIR155HG are hypomethylated, PRDM16 is hypermethylated in RA ( Glossop et al, 2015 ).…”
Section: Genome-wide Methylation Profiling To Identify Ra-associated mentioning
confidence: 99%
“…Abnormal methylation regions maybe overlapped with transcription factors binding sites (TFBS) to activate enhance regulation activities. For example, RA related hypomethylated regions are found overlap with binding motifs of transcription factors such as GLI1, RUNX2, and TFAP2A/C, and these TFs are closely related to the TGF-β pathway (Ham et al, 2019). The hypermethylation genes CCR6, CMTM5, IL10RA, IL21R and IL32 in systemic lupus erythematosus and pSS while hypomethylation in RA (Wang et al, 2018).…”
Section: Genome-wide Methylation Profiling To Identify Rheumatoid Artmentioning
confidence: 99%